Archetypical Analysis of Boston Epic - Simsek, Esma; Ozdemir, Uyesi Serdar Deniz (Geleneksel Yayincilik Ltd Stl, 2021)
The epic is one of the narrative genres that comes to life as a reflection of the collective unconscious. It is a literary form of existence that inspires all layers of culture with its multi-dimensional structure. It contributes to many thoughts synthesized on the real and imaginary plane through its symbolic elements. In this context, Boston Epic, which belongs to the Kyrgyz Turks, has a power that can spread to the consciousness in terms of imagination with its psychological / symbolic structure. The Boston Epic contains very important archetypalsymbolic data reflecting ancient wisdom. It is seen that cosmic thoughts belonging to being / human are also included in the epic, where the adventure of the symbolic hero named Boston finds meaning in a psycho-mythological universe. These thoughts, together with the archetypes that direct the maturation process, allow for a spiritually new world design. The hero's journey to maturity is in line with the stages of separation-maturation-return, referred to as the core of the monomite and systematized by Joseph Campbell. In the epic, Umay Ana, who has a very important place in Turkish culture, appears in the extraordinary birth of the hero. During the naming ceremony, Hizir has a function that reveals the imagination of soul / body. The appearance of these beings adds an important value to the mythological / symbolic structure of the epic. Boston appears to be born and raised in an extraordinary manner, in accordance with the nature of the heroic myth, as in the development of many epic heroes. He starts talking two days after he gets his name and walks on the third day. After a while, he becomes an adult human. It is possible to say that this situation makes a clear reference to the divine sacred. At the very beginning of the epic, the hero, who is represented with a crude form of existence, takes a symbolic adventure in accordance with the call to adventure. During the separation phase, he obtains the horse called Karaboz At and is a powerful reflection of the supreme individual and crosses the symbolic threshold. The hero's twin sister, Karacac, appears as a trickster figure in the test scenes that represent the most challenging aspects of the adventure. She is a negative figure that drags her brother and nation to annihilation for her own interests. The hero continues his journey to maturity despite the suppressive influence of his twin sister. Boston marries women who will support the fullness of consciousness in the process of spiritual development. Finally, with the help of his horse, he wins the maturity test after struggling with all the manifestations of darkness. Inspired by the contrast / completeness thought, he reaches the self in the test of life. In addition, he attains eternal consciousness by obtaining abihayat (the fountain of youth) that represents the purest form of mythical elements of existence. When he returns, he punishes his sister as she deserves. He brings vitality to his nation on the verge of extinction and leaves a virtuous legacy to future generations with its blessed appearance unique to khans. The elements included in all these scenes are symbolically very valuable. Analyzing these elements will provide a better understanding of some universal values. In line with this thought, in this article, the Boston Epic has been analyzed in the context of the symbolic-mythological perspective and the archetypal analysis method.
Boston destani’nin arketİpsel tahlİlİ
Keywords: Epic; archetype; symbol; Boston Epic; analysis